CHANGES IN ASCORBIC ACID LEVELS IN TISSUES OF FRESHWATER PRAWN, CARIDINA WEBERI AFTER LETHAL EXPOSURE TO ENDOSULFAN - SAROJINI, R.; YADAV, B.S.; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
Changes in ascorbic acid levels after exposure to lethal doses of pesticide endosulfan was carried out in hepatopancreas, ovary and muscle of freshwater prawn, C. Weberi. In control the ascorbic acid level was observed to be more in hepatopancreas than in ovary and muscle. After lethal exposure to concentration of 0.0288, 0.0204, 0.0173 and 0.0141 ppm of endosulfan for 24, 48,72 and 96 hours respectively, the ascorbic acid level in C. Weberi was found to be increased in hepatopancreas, ovary and muscle.